FORMULATION AND EVALUATION OF HERBAL OINTMENT CONTAINING TINOSPORA CORDIFOLIA & PSIDIUM GUAJAVA AGAINST STAPHYLOCOCCUS AUREUS BACTERIA - Dr. Tambe A.B.,; Dr. Bhawal G. S,; Varade Radika,; Unde Komal,; Tikhe Lokesh,; Urhe Prashant,; Todmal Omkar, (The Bioscan, 2025)
The present study aimed to develop and evaluate a herbal ointment containing Tinospora cordifolia and Psidium Guajava against Staphylococcus aureus. The ointment was formulated using a combination of the two plant extracts, which have been reported to possess antibacterial properties. The antibacterial activity of the ointment was evaluated using three different formulations, with Mupirocin as the standard drug. The results showed that the herbal ointment exhibited significant antibacterial activity against Staphylococcus aureus, with the most effective concentration showing a zone of inhibition of 19 mm. The study demonstrates the potential of Tinospora cordifolia and Psidium Guajava as natural antibacterial agents, and highlights the potential of the developed ointment as an alternative to conventional antibiotics.